2003
DOI: 10.1021/jp036059k
|View full text |Cite
|
Sign up to set email alerts
|

Study on the AC Impedance Spectroscopy for the Li Insertion Reaction of LixLa1/3NbO3 at the Electrode−Electrolyte Interface

Abstract: Hereunder presented is an AC impedance spectroscopic study of the lithium-inserted material Li x La 1/3 NbO 3 . Two semicircles were noted in accordance with the plots given as the complex impedance in the frequency region of 0.5 to 5000 Hz at room temperature, and these two semicircles made variation accompanied with the composition x. The dependence of the impedance spectra on the lithium salt concentration and temperature was examined, and it is explained that these two semicircles were in relation to the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 17 publications
(23 reference statements)
2
61
0
Order By: Relevance
“…In general, metal deposition in liquid electrolytes contains electron transfer from an electrode to metal ion and the following desolvation or solvent reorganization. Abe et al 16 and Uchimoto et al 17 suggested that Li/Li + couple reactions at the electrode/electrolyte interface in various organic electrolyte soutions had high activation barrier which was strongly influenced by the solvation and desolvation of Li ions. These strongly suggest that for the Li deposition in the present liquid electrolyte the desolvation step after electron transfer from the electrode to Li + ion is rate-determining.…”
Section: Resultsmentioning
confidence: 99%
“…In general, metal deposition in liquid electrolytes contains electron transfer from an electrode to metal ion and the following desolvation or solvent reorganization. Abe et al 16 and Uchimoto et al 17 suggested that Li/Li + couple reactions at the electrode/electrolyte interface in various organic electrolyte soutions had high activation barrier which was strongly influenced by the solvation and desolvation of Li ions. These strongly suggest that for the Li deposition in the present liquid electrolyte the desolvation step after electron transfer from the electrode to Li + ion is rate-determining.…”
Section: Resultsmentioning
confidence: 99%
“…This result confirms that semicircle A is attributable to the desolvation process according to the adatom model. 7,8 In contrast, the activation energy for semicircle B does not depend on whether EC + DEC or GBL is used as the solvent and does depend on the voltage; that is, the chemical potential of Li + , where the activation energy increases as the voltage is increased. Therefore, semicircle B does not originate from the properties of these electrolytes, but from the surface properties of the electrode material.…”
Section: Experimentmentioning
confidence: 99%
“…We thus conclude that semicircle B corresponds to the lattice incorporation process on the basis of the adatom model. 7,8 ■ DISCUSSION In the adatom model, two factorsdesolvation (semicircle A) and lattice incorporation (semicircle B)affect the Li + exchange at the electrode/electrolyte interface. Although the physicochemical interpretation is clear with respect to the desolvation process, there are ambiguities with respect to lattice incorporation.…”
Section: Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first used to depict the lithium ions insertion/desertion process of LiTiS 2 by Bruce [19,20] in the lithium-ion battery field, and then was developed by Kobayashi as well as many others [40,71,76,114]. In this model, the intercalation reaction proceeds in several steps, as shown in Figure 2-1: a solvated cation in solution adjacent to the electrode loses part of its solvation sheath and becomes adsorbed, thus forming an adion, on the electrode surface, accompaning by the injection of an electron into the conduction band of the solid host.…”
Section: Kinetic Models For Lithium Ions Insertion Into the Intercalamentioning
confidence: 99%